MERINTIS PELAYANAN KELOMPOK KECIL CARE CELL DAN GEREJA CABANG GEREJA BETHEL INDONESIA PASIR KOJA DI CIMAHI - Ferry Simanjuntak; Jeremy Deo; Joseph Patria Christi; Jeremy Mulyadi; Jonathan Aristo (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2022)
Abstract The development of Cimahi city in education, trade and industry allows the flow of urbanization to the city of Cimahi from various regions in Indonesia, including from the Nias islands and North Sumatra province with a Christian background. This allows the establishment of faith development services in a small group called Care Cell as well as pioneering the church branch of Bethel Indonesia Pasir Koja Church (GBI Pasko) Bandung as a place to be shepherded. Considering that Kharisma Theological College has the goal to prepare students for the task of pioneering the church, grazing (Ministry) then GBI Pasko and STT Kharisma Bandung cooperate in pioneering care cell services in Cimahi. The Church is a living organism inhabited by the Holy Spirit, just as all other organisms are always growing and multiplying, so the church as a living organisema continues to grow in both quality and quantity. One way congregations are apostasy is by placing and serving them in small group discipleship and in the context of GBI Pasko, this small group discipleship is named Care Cell. Keywords: Pioneering, Discipleship, church